Basic Body Metabolism Rate and Its Relationship With Lactic Acid Concentration in Judokas aged 18 – 21 years old - Tariq, Oday; AbdElkhalek, Sirhank; Ahmed, Ali (Journal of Physical Education, 2013)
The research aims at identifying the relationship between basic body metabolism and lactic acid concentration in youth judo players of the ages 18 – 21 years old. The problem of the research was heavily relaying on training programs without specifying the amount of intensity according the basic body metabolism rate and lactic concentration in judokas of the ages 18 – 21 years old. In chapter two, the systems of energy, lactic acid concentration and basic body metabolism are defined. Chapter three tackled the methodology of the research. The researchers used the descriptive method and the subjects were 10 national judo league judokas. The basic metabolism was measured using metabolism law as well as lactic acid measuring device. Lactic acid is measured after five minutes from the end of the training session’s first part. After conducting a pilot study, the data was collected and treated using proper statistical methods namely, SPSS. In chapter four, the data are displayed, analyzed and discussed. The researchers concluded that lactic acid concentration id related to basic body metabolism. Finally, they recommended paying attention to biochemical and functional variables in preparing a training program especially the concentration of lactic acid in blood after fatigue using direct and field measuring to collect accurate scientific results.